People's Labor Traditions in The Process of Labor Preparation for Schoolchildren - Khaydarov, M.E.; Lukhmanov, D.B. (International Journal of Psychosocial Rehabilitation, 2020)
The questions of national labor traditions in the process of labor training of younger students are considered. National traditions of the popular educational system require the direct participation of the younger generation in the productive work of adults, considering this as the most effective way of labor education in Uzbekistan.